Keutamaan Sedekah dalam Perspektif Hadis - Maftuhi Mamduh; Salim Rosyadi; Nur Iskandar (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Alms is one of the obligations carried out by a Muslim who has excessive wealth. Those who are obliged to give alms to those who are entitled to receive it. This is because the recommendation from the Koran and Sunnah to give alms is not binding. The discussion in it explains the hadith regarding the virtues of almsgiving. The method used in the research is hadith thematic with a grounded theory approach. The hadiths found were 8 hadiths, namely the history of Bukhari, Muslim, and An-Nasa'i. This research concludes that almsgiving is something that Muslims must do because it will bring many benefits to those who do almsgiving, and there are many rewards to be gained.